Iqbal’s Vision and the Dignity of the Human Race - Niaz, Shabnam; Khan, Shaista Hameed (sourcecoder, 2024)
Dr. Mohammad Iqbal needs no introduction. He was not only a great poet but a thinker a philosophy and genius too. His strong intellect and insight are clearly seen in his poetry. Iqbal’s vision serves as a mirror, reflecting vividly the present and the future of the Muslim Ummah. He not only foresees the future predicaments but also suggest a way out. In his poetry, Iqbal frequently discusses the effects of humanitarian values. He stress that the success and elevation of the ummah lies in humanitarianism. In many places he states features of dignity of the human race. The paper under elucidates the idea of the dignity of the human race as ennisaged by Iqbal.